Carboxylate‐Assisted Iridium‐Catalyzed C−H Amination of Arenes with Biologically Relevant Alkyl Azides. Issue 9 (28th January 2016) - Zhang, Tao; Hu, Xuejiao; Wang, Zhen; Yang, Tiantian; Sun, Hao; Li, Guigen; Lu, Hongjian
Abstract: An iridium‐catalyzed C−H amination of arenes with a wide substrate scope is reported. Benzamides with electron‐donating and ‐withdrawing groups and linear, branched, and cyclic alkyl azides are all applicable. Cesium carboxylate is crucial for both reactivity and regioselectivity of the reactions. Many biologically relevant molecules, such as amino acid, peptide, steroid, sugar, and thymidine derivatives can be introduced to arenes with high yields and 100 % chiral retention. Abstract : Ir responsible ! A direct C−H amination between benzamide derivatives and various alkyl azides was achieved using iridium catalysis (see scheme; NTf=trifluoromethanesulfonyl amide). Cesium carboxylate was found to be the promoter and regiocontroller of this reaction. By this method, many biological active molecules can be introduced to benzamide components with high yields and 100 % chiral retention.